Political Attributes of Millennials in a State University in Zambales, Philippines - Ebro, Eric DS. (Future Science / FSH-PH Publications, 2021)
The study revisited the political culture of millennials, promising citizens, and leaders of the country. It described and explored the perceptions and outlooks of millennials towards knowledge, involvement, and values as attributes of political culture. The study was a descriptive survey and correlational design. The study revealed that most millennials depend on TV and social media as sources of political information and consider integrity, honesty, intelligence, and experience to vote for a candidate in an election. Meanwhile, there is a significant difference among the three political attributes as shown in the computed F-value of 56.94; millennials have the highest level of attributes in political values compared with political knowledge and involvement. Interestingly, the result indicates no significant difference between the male and female levels of political attributes. On the other hand, the computed F-value of 3.05 showed an apparent significant difference in political attributes of millennials when grouped according to religion. Generally, millennials have a high level of political attributes; this indicated that despite that millennials were in the midst of the fast-changing world brought by media and technology, they stay active citizens as seen in their political values that remain highly intact.